Behavioral Biases Influencing Investment Decisions of Life Insurance Investors - Shunmugasundaram, V.; Sinha, Aashna (International Journal of Economics and Financial Issues, 2022)
The purpose of this paper is to validate the scale of behavioral biases and investment decisions concerning investors of life insurance and to evaluate the impact of behavioral biases on investment decisions made by them. The study is based on a questionnaire survey by including the investors of life insurance residing in Bihar (India) using a convenient sampling technique. The collected data were analyzed using SmartPLS. The study found that the scale used to measure behavioral biases and investment decisions of investors of life insurance were valid and behavioral biases have a positive and significant impact on investment decisions of life insurance investors. The study found that the investors are behaviorally biased while making investment decisions related to life insurance and only four biases are included in the study. The study contributes to the academia of behavioral aspects of life insurance investors. The study helps in understanding the mindset of investors investing in life insurance. This study contributes to the limited study undertaken in the area of behavioral aspects of life insurance investors. It also contributes to the lacking academe of life insurance.